TOTAL OXIDANT AND ANTIOXIDANT LEVELS IN PATIENTS WITH GALLBLADDER STONES OR RELATED COMPLICATIONS: ARE THEY IMPORTANT FOR TREATMENT? - ÇELIK, Muhammed Emin; SOYLU, Veysel Garani; YILMAZ, Ayse (FapUNIFESP (SciELO), 2024)
ABSTRACT BACKGROUND: Many free radicals result in an inflammatory process due to complications caused by gallstones. These free radicals are inactivated by various reactions and participate in different reactions. Molecules are oxidants and antioxidants that take an active role in almost every event that takes place in the body. AIMS: To analyse the changes in total antioxidant level (TAL) and total oxidant level (TOL) in the follow-up of patients hospitalized for cholelithiasis or its complications, showing the active oxidative stress, and to test the usability of these parameters in the evaluation of treatment success. METHODS: Forty-five patients took part in the study. Blood samples were taken twice, previous to surgery and 6 hours after surgery. Tissue samples were also obtained from patients who were operated. Then, the samples were sent to a laboratory to measure the total oxidant and antioxidant status of patients. RESULTS: The median for the TAL_before (pre-operation or hospitalization in non-operational) variable was 2.40 (interquartile range — IQR=0.50), and the median for the TAL_after variable was 2.20 (IQR=0.33). The median of the tissue-derived TAL variable was 0.32 (IQR=0.13), and the median of the TOL variable was 0.43 (IQR=0.52). The median value of the TAL_before variable for men was 2.50 (IQR=0.50), while the median value for the TAL_before variable for women was 2.30 (IQR=0.50). TAL_before variable values did not show a statistically significant difference according to gender (Z=1.446; p=0.154, p>0.05). Similarly, the median values of TOL_before variable by gender were similar (Z=0.614; p=0.545, p>0.05). CONCLUSIONS: Cholelithiasis and its complications cause many inflammatory responses, ending with free radical formation. During follow-up, its level decreases due to consumption or success of the treatment.
Keywords: Male; Adult; Oxidative Stress; Humans; Original Article; Female; Gallstones; Middle Aged; Oxidants; Antioxidants; Aged